2017
DOI: 10.2214/ajr.17.18339
|View full text |Cite
|
Sign up to set email alerts
|

Trainees May Add Value to Patient Care by Decreasing Addendum Utilization in Radiology Reports

Abstract: Trainees may add value to patient care by decreasing addendum rates in radiology reports.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The power of double reading in the trainee-and-attending radiologist dyad model was highlighted in a recent study by Balthazar et al (21), which showed that radiology reports generated without trainee involvement were up to 12 times more likely to include a later addendum than were reports with trainee involvement. The need for an addendum is generally indicative of the presence of one or more errors in the radiology report that were discovered only after the report was finalized by an attending radiologist.…”
Section: Cost and Cost-effectivenessmentioning
confidence: 99%
“…The power of double reading in the trainee-and-attending radiologist dyad model was highlighted in a recent study by Balthazar et al (21), which showed that radiology reports generated without trainee involvement were up to 12 times more likely to include a later addendum than were reports with trainee involvement. The need for an addendum is generally indicative of the presence of one or more errors in the radiology report that were discovered only after the report was finalized by an attending radiologist.…”
Section: Cost and Cost-effectivenessmentioning
confidence: 99%
“…Several studies in the past have used different methods and study populations to analyze radiological error rates and have obtained variable results ( Table 4 ). 1 8 9 10 11 12 13 14 15 16 This is because of the absence of a single, standard, and universally reproducible process of analyzing radiological errors.…”
Section: Discussionmentioning
confidence: 99%
“…There is limited literature that evaluates report addenda as a tool for error analysis, summarized in Table 4 . 1 8 9 10 One such noteworthy work by Brigham et al 8 used report addenda to calculate error rates in 5,568 reports and classified them based on etiology and image modality. These studies reflect an agreement that addenda analysis as a self-acknowledged method of error detection is less time consuming and minimizes the interobserver variability in image interpretation compared with the peer review method in previous works.…”
Section: Discussionmentioning
confidence: 99%